Histochemical studies of the common bile duct in reindeer - Rahko, Timo; Nikander, Sven (Rangifer, 1990)
Histochemical characteristics of bile duct mucosubstances, mast cells and globule leucocytes have not previously been described in the reindeer. Therefore various staining methods were applied on 1 to 6 specimens cut from formaline or Bouin-fixed histological blocks of the ductus hepaticus communis from 20 reindeer. The present study showed that bile duct mucins include neutral, carboxy- and sulphomucins located chiefly in goblet cells and in the deep glands and as a thin superficial layer covering the surface epithelium. PAS-reactivity was diastase resistant, indicating that glycogen was not demonstrable in the epithelial layer of reindeer, contrary to previous studies e.g., on carnivores. Furthermore, carboxymucins were sialidase-resistant, as sialic acid could not be identified in the present material. Certain differences were noted in the appearance and composition of intracytoplasmic granules and globules of mast cells and globule leucocytes, respectively. The mucosubstances of the mast cell contained sulphate groups indicative of sulphomucins while both neutral, carboxy- and sulphomucins were identifiable in globule leucocytes. However, due to the sensitivity of mast cells and globule leucocytes to postmortal changes the above interpretations need to be confirmed by further studies.Histokemiallinen tutkimus yhteisen sappikaytavan rakenteesta porolla.Abstract in Finnish / Yhteenveto: Yhteisen sappikaytavan (ductus hepaticus communis) seinaman epiteelisolukon ja syotto- ja kerassolujen lima-aineiden koostumusta porolla ei ole aikaisemmin kuvattu. Sen vuoksi katsottiin aiheelliseksi suorit-taa histokemiallinen tutkimus formaliini- ja Bouin-kovetetusta histologisesta aineistosta, jonka kirjoittajat ovat julkaisseet aikaisemmin. Aineisto on peraisin 20 porosta. Erilaisia histokemiallisia varjayksia sovellettiin 1-6:een valikoituun leikkeeseen tarkoituksella analysoida nimenomaan lima-aineiden koostumusta. Tutkimuksissa ilmeni, etta sappikaytavien erittama lima koostuu neutraaleista, karboksy- ja sulfomusiienista. Eritys tapahtuu paaasiassa pikarisoluista ja seinamien syvista rauhasista. Myos pintasolukkoa peittaa ohut limakerros. Glykogeenia ja sialiinihappoa ei todettu. Syotto- ja kerassolujen soluliman jyvasten koostumuksessa todettiin tiettyja eroavaisuuksia. Syottosolujen lima-aineet ovat sulfomusiineja, mutta kerassolujen jyvasissa on sulfomusiinien lisaksi myos neutraaleja- ja karboksymusiineja. Syotto- ja kerassolujen todettiin olevan herkkia kuolemanjalkeisille muutoksille, mika vaikeutti varmojen johtopäätosten tekemistä.Histokemiska studier av gallgången hos ren.Abstract in Swedish / Sammandrag: Mucinernas sammasättning i globulära leukocyter, mast- och epitelceller i gallgångarna på ren har inte beskrivits tidigare. Det ansågs motiverat att histokemiskt undersöka det formalin- och Bouin fixerade material som tidigare publiserats av undertecknade. Materialet härstammar från 20 renar. Olika histokemiska färgningar utfördes på 1-6 utvalda preparat i avsikt att analysera muchinernas sammansättningen. Det framgick att slemmet i gallgången innehåller neutrala-, karboxyl- och sulfomuciner. Exkretionen sker i huvudsak från bägarceller och körtlar i gallgångvaggen. Ytepitelet täckes också av et tunnt slemskit. Glykogen och sialinsyra påvisades icke. Det konstaterades skillnader i mucinsammansättningen hos mastceller och globulära leukocyter. I mastcellernas granulae påvisades sulfomuciner och de globulära leukocyterna innehöll förutom sulfomuciner, neutrala- och karboxymuciner. Konklusionerna bör vérifieras medan mastcellerna och de globulära leukocyterna föreföll att var känsliga för postmortal förändringer.